Quality of patient-reported and proxy-reported outcomes for children with impairment of the lower extremity: systematic review protocol - Denise Eygendaal; Tim Saris; Ruben Kalle; Inger Sierevelt; Christiaan van Bergen (BMJ Publishing Group, 2022)
Introduction As patient-reported outcome measures (PROMs) have become of significant importance in evaluation of care and clinical research, adequately selecting the appropriate instrument is an integral part of paediatric orthopaedic research and clinical practice. This systematic review aims to provide a comprehensive overview of PROMs targeted at children with impairment of the lower limb, and to critically appraise and summarise the quality of their measurement properties by applying the COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) methodology.Method and analysis A systematic search of the MEDLINE and EMBASE databases will be performed to identify relevant publications reporting on the development and/or validation of PROMs used for evaluating children with impairment of the lower extremity. Data extraction and quality assessment of the included studies will be undertaken by two reviewers independently and in accordance with COSMIN guidelines.Ethics and dissemination It is not necessary to obtain ethical approval for this systematic review. The results will be published in a peer-reviewed journal and will be presented at relevant conferences to enhance information dissemination.PROSPERO registration number CRD42021287323.